Membumikan Nilai-Nilai Toleransi Al Quran dalam Kehidupan Multikultural Masyarakat Desa Pringombo Kecamatan Tempuran Kabupaten Magelang - Ahmad Amin; Ahmad Mustofa; Titis Rosowulan (Syntax Idea)
This study aims to identify and analyse the values of tolerance contained in the Qur'an and how these values are implemented in the daily lives of multicultural communities in Pringombo Village. This Living Qur'an study uses a qualitative research method with a descriptive approach. Data were collected through participatory observation, in-depth interviews with community leaders, religious leaders, and the general public, as well as documentation studies. The results showed that tolerance values such as mutual respect, appreciation of differences, peaceful coexistence, and cooperation in goodness, are very much embedded in the lives of the people of Pringombo Village. The implementation of these values is seen in various aspects of life, such as joint religious activities, mutual cooperation, and conflict resolution. In conclusion, the Qur'an provides a strong foundation for the people of Pringombo Village to coexist harmoniously in diversity. The values of tolerance taught in the Qur'an have become an integral part of community life and contribute to the creation of religious harmony.